Marketing Collaboration and SME Strategy Implementation in Blora, Indonesia - Widjajanti, Kesi (UI Scholars Hub, 2021)
The collaboration between small and medium enterprises (SMEs) and large enterprises (LEs) have been widely researched. Previous research on collaborative marketing strategy has been developed, but the contribution of these strategies for SMEs is still unclear. This research focuses on “marketing collaboration”to clarify the role of collaboration, based on the discussion of the findings that emerged from the qualitative study of SMEs. This is related to the characteristics of creative industries which mostly consist of SMEs with limited knowledge and skills to enter in the field of marketing. To expand the business SMEs is very difficult if done alone. To accelerate the development of its business, SMEs need to collaborate with an LEs which has a marketing network. Marketing collaboration between SMEs and LEs to be one effective way to develop business, as both sides can increase profitability. While LEs can improve technological innovation other hand, SMEs receive various benefits such as access to technology and access to new markets.